ADVANTAGES AND DISADVANTAGES OF USING STABLE COINS AS A TOOL FOR REDUCING CRYPTOLEUR VOLATILITY IN THE FINANCIAL MARKET (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Cryptocurrencies are characterized by high volatility. This is primarily due to the fact that this market is relatively young with a small number of participants and trading volumes. If there is a flow of public information in traditional markets, regular corporate reporting in accordance with international standards, reporting of regulators on macroeconomic indicators, forecast estimates of analysts on the current and future state of the markets. In the field of cryptocurrencies, such an environment is just being formed. This leads to the fact that cryptocurrency rates (mostly in dollar terms) are prone to high levels of volatility, which makes their use inconvenient from a practical point of view as a means of exchange and value.At the same time, the volatility of bitcoin and other cryptocurrencies in the financial market prevents the use of these digital assets as money. In addition to instruments to mitigate the currency risk of using existing cryptocurrencies, new cryptocurrencies are being developed that are specially designed so that their market exchange rates have low volatility for an asset. Such cryptocurrencies are called stablecoins.Stablecoin or stablecoin is a cryptocurrency whose price depends on the value of a traditional financial asset. It can be the US dollar, oil, gold, etc.In our opinion, stablecoins are a new, hybrid type of digital assets, which combines innovative mechanisms of direct cost exchange and management of financial transactions without the participation of intermediaries with centralized issuance mechanisms and the use of various methods to ensure price stability of financial assets. In a general sense, stablecoins are cryptocurrencies that: 1) are issued by an identified issuer on a blockchain in the form of digital commitment or depository receipts; 2) maintain exchange rate stability by pegging to the basic low-volatility monetary or commodity supply, or by using algorithmic technologies; 3) can be used as a means of saving or exchanging in modern conditions.
Keywords: cryptocurrency, cryptocurrencies, digital tokens, money, volatility, stablecoins.